The Effect of Heat Treatment and Chemical Treatment on Natural Fibre to The Durability of Wood Plastic Composites – A Review - Nasharudin, Nuratiqah Asyiqin Mohd; Sulaiman, Nur Fatihah; Mohammad, Nurul Aziemah; WAN JAAFAR, WAN NOR RAIHAN; Abu, Falah, Dr.; Surip, Siti Norasmah (Journal of Materials Exploration and Findings, 2023)
The application of WPC is not only limited to indoor applications but has been extended to exterior applications where properties of WPC could compromise during service life. WPC was derived from wood fiber of various sizes to reinforce polymers. Wood fiber has the advantage of a cheaper price, being abundantly available, and ease of processing, however, the critical factor is its hydrophilic nature, where moisture absorption is likely to occur. Thus, treatments for reducing the hydrophilicity of wood fibers are applied. By treatment of wood fiber, the surface impurities were removed, leaving the roughened surface of fibers, thus providing a good surface for fiber-matrix interaction. The purpose of this study is to systematically review the effect of heat treatment and chemical treatment on wood fiber on the durability of WPC. The literature cited was searched in Scopus with related keywords – leading to 4292 articles. Article search was then limited from 2012 to 2021 and led to 443 articles to identify and analyze focusing on the durability of WPC. After fine-tuning, only 30 articles were considered to answer the research question in this study. The finding reveals that the treatment of wood fiber has a significant effect on the durability of WPC. Heat and chemical treatment were observed to improve the interfacial adhesion and resistance to fungal attack and the mechanical and physical properties of WPCs.